1996
DOI: 10.1097/00007890-199604270-00005
|View full text |Cite
|
Sign up to set email alerts
|

31p Nuclear Magnetic Resonance Study of Phospholipids in Ischemia/Reperfusion Injury in a Rat Fatty Liver Model

Abstract: Obese Zucker rats are susceptible to increased hepatic ischemia/reperfusion (I/RP) injury. Increased lipid peroxidation occurs in this model with warm ischemia. We hypothesized that a severe depletion of phospholipids (PL) occurs with warm I/RP in fatty livers. Obese (Ob) and lean (Ln) Zucker rats were subjected to 90 min of in vivo partial hepatic warm I followed by RP. Total lipids extracted from one gm of liver (median lobe) taken at the end of 1, 2 and 6 hr of RP and sham (Sh) surgery (n=5 Ln & Ob) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Support for this concept is provided by previous observations of decreased liver phospholipids and increased lipid peroxidation products, in rat fatty livers, during reperfusion following warm ischemia. 8,9,34 Further support is provided by the significant increase in survival of animals in antioxidant groups I and III, groups that received additional TOC following reperfusion. TOC protects membranes from free radical attack and, in the process, becomes oxidized to tocopheroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this concept is provided by previous observations of decreased liver phospholipids and increased lipid peroxidation products, in rat fatty livers, during reperfusion following warm ischemia. 8,9,34 Further support is provided by the significant increase in survival of animals in antioxidant groups I and III, groups that received additional TOC following reperfusion. TOC protects membranes from free radical attack and, in the process, becomes oxidized to tocopheroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…Steatotic livers substantially contribute to the donor pool, thereby partially compensating for organ shortage. Clinical and experimental studies have shown that steatotic livers are more susceptible to IRI than lean livers [3,4,[22][23][24][25] . This results in increased plasma aminotransferases and diminished liver function in the early postoperative phase following transplantation [3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…Some activation of intracellular cascade for signal transmission is included and is connected to the final pathway for de novo synthesis of HSP72 [29]. It is known that steatotic liver is more sensitive to harmful stresses than normal liver [4,30]. Fat deposition may possibly change the intracellular environment.…”
Section: Discussionmentioning
confidence: 99%